The death mechanism of the harmful algal bloom species Alexandrium tamarense induced by algicidal bacterium Deinococcus sp. Y35 - Li, Yi; Zhu, Hong; Lei, Xueqian; Zhang, Huajun; Cai, Guanjing; Chen, Zhangran; Fu, Lijun; Xu, Hong; Zheng, Tianling (Frontiers in Microbiology, 2015)
Abstract: Harmful algal blooms (HABs) cause a variety of deleterious effects on aquatic ecosystems, especially the toxic dinoflagellate Alexandrium tamarense, which poses a serious threat to marine economic and human health based on releasing paralytic shellfish poison into the environment. The algicidal bacterium Deinococcus sp. Y35 which can induce growth inhibition on A. tamarense was used to investigate the functional mechanism. The growth status, reactive oxygen species (ROS) content, photosynthetic system and the nuclear system of algal cells were determined under algicidal activity. A culture of strain Y35 not only induced overproduction of ROS in algal cells within only 0.5 h of treatment, also decrease the total protein content as well as the response of the antioxidant enzyme. Meanwhile, lipid peroxidation was induced and cell membrane integrity was lost. Photosynthetic pigments including chlorophyll a and carotenoid decreased along with the photosynthetic efficiency being significantly inhibited. At the same time, photosynthesis-related gene expression showed down-regulation. More than, the destruction of cell nuclear structure and inhibition of proliferating cell nuclear antigen related gene expression were confirmed. The potential functional mechanism of the algicidal bacterium on A. tamarense was investigated and provided a novel viewpoint which could be used in HABs control.